The Theatrical Periodical and Newspaper Library in Zagreb – an Overview of Its Contents - Maroshi, Drita (Poznańskie Studia Slawistyczne, 2020)
This paper aims to present the contents of the Periodical and Newspaper Library of the Croatian Academy of Sciences’ Division of the History of the Croatian Theatre from the 1921–1924, 1968– 1969, and 1989–1992 periods, i.e. on a sample of nine theatre seasons. It includes an overview of the newspapers and periodicals from which the Library’s contents originate as well as of the number of articles in each of the specified periods, i.e. theatre seasons. The research presented here encompasses 10,859 articles, which have been classified; data on the types of articles present in each period has been tabulated. Even though a comparison of results shows that the number of sources – i.e. newspapers and other periodicals from which the Library’s contents are gathered – was significantly reduced, this did not influence the larger deviations in the overall number of articles in the researched periods. The paper shows that authored articles – mostly critiques – are the predominant type in all the researched periods, offers an insight into the diversity and wealth of the Library’s contents, and refers to the differences and similarities regarding the types and prevalence of articles in the examined periods.